Comparison of Species Richness and Availability of Wild Food Plants and Fungi Sold in Two Open-Air Markets in Stung Treng Province, Cambodia - Naven Hon; Alison M. Behie; Tim Denham; Kimchhin Sok; Jessica M. Rothman (Ethnobotany and Economic Botany, 2026)
Wild food plants play a vital role in food sources in many rural communities. This study examines the diversity, species richness, and seasonal availability of wild food plants and edible fungi sold in two markets in Cambodia. The Stung Treng market is located in the provincial center, whereas the Siem Pang market is situated near protected areas. Fieldwork was conducted from March to December 2024, and from January to March 2025. Species richness and asymptotic richness analyses were used to compare market composition and sampling completeness. A total of 100 wild food plants were recorded. Species richness was significantly higher in the Stung Treng market than in the Siem Pang market. This demonstrates that proximity to protected areas does not necessarily result in higher wild food plant diversity in local markets. Instead, markets located farther away—particularly those in central provincial capitals—can exhibit greater species richness. Seasonal patterns were evident, although several species remained available year-round. These seasonal fluctuations suggest that local markets help buffer food systems by maintaining access to diverse wild foods. Species accumulation analyses indicated that additional survey days may reveal a few rare species; however, this study likely captured the majority of the commonly traded species.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Site formation processes of outdoor spaces in tropical environments: A micro-geoarchaeological case study from backyard Lo Gach, southern Vietnam - Elle Grono; David E. Friesem; Rachel Wood; Tim Denham; Nguyen Khanh Trung Kien; Dang Ngoc Kinh; Philip J. Piper (Archaeological and Anthropological Sciences, 2022)

Fahien reconsidered: Pleistocene exploitation of wild bananas and Holocene introduction of Musa cultivars to Sri Lanka - Edmond De Langhe; Luc Vrydaghs; Xavier Perrier; Tim Denham (Journal of Quaternary Science, 2019)
A recent publication on the phytolith assemblage at Fahien rockshelter, Sri Lanka (Premathilake and Hunt) is argued to represent: the exploitation of wild Musa acuminata and M. balbisiana during the Late Pleistocene; the introduction of edible diploid cultivars from the Southeast Asia–New Guinea region during the early to mid‐Holocene; the generation and cultivation of triploid banana hybrids on Sri Lanka before 6194–5994 cal bp ; and the subsequent spread of derived triploid cultivars to mainland India and westward to Africa. A careful review of the archaeobotanical research presented by Premathilake and Hunt, in the context of broader multidisciplinary evidence (agronomy, archaeobotany, genetics and linguistics) for the domestication and spread of banana cultivars, indicates that three main aspects of their argument are problematic: the lack of clarity in the characterization of banana domestication in the past; the methods used to discriminate phytoliths into banana taxa; and the promotion of Sri Lanka as a source region rather than a recipient of banana cultivars. Following reconsideration, the Fahien evidence is consistent with previous interpretations for the origins of diploid and significant triploid cultivars outside of Sri Lanka and dispersal to that island. © 2019 John Wiley & Sons, Ltd.

An assessment of microCT technology for the investigation of charred archaeological parenchyma from house sites at Kuk Swamp, Papua New Guinea - Jenifer Pritchard; Tara Lewis; Levi Beeching; Tim Denham (Archaeological and Anthropological Sciences, 2019)

Traditional forms of plant exploitation in Australia and New Guinea: the search for common ground - Tim Denham (Vegetation History and Archaeobotany, 2008)